Physicochemical properties and oxidative stability of duck fat-added margarine for reducing the use of fully hydrogenated soybean oil. (30th November 2021) - Shin, Dong-Min; Yune, Jong Hyeok; Kim, Tae-Kyung; Kim, Yea Ji; Kwon, Hyuk Cheol; Kim, Do Hyun; Jeong, Chang Hee; Choi, Yun-Sang; Han, Sung Gu
Highlights: Duck fat was used in margarine manufacturing to reduce the use of trans fatty acids. Addition of duck fat improved the physicochemical properties of margarine. Addition of duck fat improved the oxidative stability of margarine. Duck fat can replace soybean oil and reduce the use of fully hydrogenated soybean oil. Abstract: Soybean oil (SBO) and fully hydrogenated soybean oil (FHSBO) have been used for margarine production. However, SBO-based margarine requires a considerable amount of trans fatty acid-containing FHSBO due to its low melting point. We aimed to reduce the FHSBO content in margarine by employing duck fat, which has a higher melting point than SBO. Margarines were prepared using different ratios of duck fat and reduced levels of SBO and FHSBO. Physicochemical, sensory, and oxidative properties of the margarines were evaluated. The quality characteristics of margarine improved when duck fat replaced SBO and FHSBO. Furthermore, the lipid oxidation parameters were lower in duck fat-added margarines than the control during storage at 60 °C for 28 days. The margarine containing 80% duck fat showed the best sensory properties. Collectively, duck fat can replace SBO in margarine while reducing the use of FHSBO and maintaining desirable physicochemical properties, oxidative stability, and sensory properties.